PENGARUH KONSTRUKSI KAIN TERHADAP KUALITAS BATIK DENGAN TEKNIK WET ON WET (WOW) - Apriliani, Silviana Silvan (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2014)
Teknik Wet On Wet (WOW) merupakan terapan pada lukisan cat air diatas kertas ataua kanfas yang basah. Pembuatan batik WOW ini pada dasarnya menggunakan bahan yang sama ketika membuat batik pada umumnya. Kain merupakan salah satu bahan dasar yang dibutuhkan untuk membatik. Kain umumnya menggunakan kain mori, kain mori merupakan jenis kain katun, yaitu kain yang bahan bakunya dari serat kapas. Kain katun mempunyai konstruksi yang berbeda. Penelitian ini mengungkapkan bagaimana konstruksi kain katun yang dipilih, dan bagaimana menentukan kualitas batik WOW pada kain katun ini. Kemudian apakah ada pengaruh konstruksi kain terhadap kualitas batik WOW. Penelitian ini bersifat Deskriptif Kuantitatif. Sampelnya adalah jenis kain katun. Metode analisis data menggunakan analisis Deskripstif Presentase. Hasil penelitian menunjukkan bahwa tidak ada pengaruh konstruksi jenis kain terhadap ketuaan warna dan ada pengaruh konstruksi jenis kain dengan efek WOW. Wet on Wet (WOW) technique is an application in water colored painting on a wet paper or fabric. The making of WOW is basically use the same material when make batik as a general rule. Fabric is a kind of basic material which is needed to make batik. Generally, fabric uses mori fabric, mori fabric is a kind of cotton fabric, this is a fabric that is made from cotton fiber. Cotton fabric has a different construction. This research reveals how is cotton fabric construction is chose, and how does determine the quality of WOW batik in this cotton fabric. Then, is there any fabric construction effect toward to WOW batik quality. This research is quantitative descriptive research. The sample is cotton fabric. Data analysis method uses percentage descriptive analysis. The result of the research shows that there is no fabric construction effect toward to colour darkness and there is fabric construction effect with WOW effect. Wet on Wet (WOW) technique is an application in water colored painting on a wet paper or fabric. The making of WOW is basically use the same material when make batik as a general rule. Fabric is a kind of basic material which is needed to make batik. Generally, fabric uses mori fabric, mori fabric is a kind of cotton fabric, this is a fabric that is made from cotton fiber. Cotton fabric has a different construction. This research reveals how is cotton fabric construction is chose, and how does determine the quality of WOW batik in this cotton fabric. Then, is there any fabric construction effect toward to WOW batik quality. This research is quantitative descriptive research. The sample is cotton fabric. Data analysis method uses percentage descriptive analysis. The result of the research shows that there is no fabric construction effect toward to colour darkness and there is fabric construction effect with WOW effect.